Experimental research in the field of creation of a two-stroke engine under similar conditions of use - Kuanyshev М.К.; Kaukarov А.К.; Saukhanov Н.С.; Murzagaliev А.Ж.; Bakyt Ғ.Б. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
The article applies to similar conditions of use and the creation of a competitive two-stroke engine. Currently, there are prerequisites for creating an effective two-stroke engine, such as direct-flow scavenging, a valve-slotted gas distribution system with a multi-valve mechanism, hydraulic valve control, a diesel cycle with a high compression ratio, etc. To implement a set of promising technical solutions, a design basis is required, on the basis of which a two-stroke engine can be configured. As such, a crank-yoke kinematic mechanism for converting motion was chosen. The mechanism unloads the piston from lateral forces and allows the cylinder to be isolated from the oil sump, using the sub-piston volume as a purge pump. This required the development and research of a cylinder-piston group based on solid lubricant. The sliding bearing has also been improved with improved quality indicators based on the use of thermally conductive and antifriction materials of copper and graphite.